Chain Model Based On Maqasid Syariah And Sdgs: Digital Economic Empowerment Strategy For Women Victims Of Child Marriage In Lombok - Benny Sultan; Deva Nabilah; Khadijatul Musanna; Deva Yulinda (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Child marriage in Lombok is still a serious problem that strengthens the structural marginalization of women through school dropouts, economic dependence, and low access to the digital economy. Various empowerment programs have been implemented, but there is no model that integrates the values of Maqasid Sharia, the Sustainable Development Goals (SDGs), and a comprehensive digital economy empowerment strategy. This research aims to construct and validate the Chain Model based on Maqasid Syariah and SDGs as a digital economy empowerment strategy for women victims of child marriage in Lombok. The research uses a qualitative approach with an instrumental case study method. The data was obtained through in-depth interviews with 24 informants consisting of women victims of child marriage, religious leaders, program facilitators, and policy makers, and strengthened through focus group discussions and document analysis. The analysis was carried out using thematic analysis with a gender perspective. The results of the study show that women victims of child marriage face economic vulnerability, low digital financial literacy, and high risk of digital economy exploitation. The Chain Model developed integrates the five principles of Maqasid Syariah with the target of SDGs 1, 4, 5, and 8 through seven systematic intervention chains. This model has been proven to strengthen digital financial literacy, increase economic confidence, and expand women's participation in digital platform-based micro-enterprises. These findings offer a contextual, sustainable, and relevant empowerment model as a basis for strengthening policies for women victims of child marriage.